Point-of-care application of diaphragmatic ultrasonography in the emergency department for the prediction of development of respiratory failure in community-acquired pneumonia: A pilot study - Chu, Sheng-En; Lu, Jian-Xun; Chang, Shi-Chuan; Hsu, Kuang-Hung; Goh, Zhong Ning Leonard; Seak, Chen-Ken; Seak, Joanna Chen-Yeen; Ng, Chip-Jin; Seak, Chen-June (Frontiers in Medicine, 2022)
Background: Early recognition of community-acquired pneumonia (CAP) patients at risk of poor outcomes is crucial. However, there is no effective assessment tool for predicting the development of respiratory failure in CAP patients. Diaphragmatic ultrasonography (DUS) is a novel technique developed for evaluating diaphragmatic function via measurements of the diaphragm thickening fraction (DTF) and diaphragm excursion (DE). This study evaluated the accuracy of DUS in predicting the development of respiratory failure in CAP patients, as well as the feasibility of its use in the emergency department (ED) setting. Methods: This was a single-center prospective cohort study. We invited all ED patients aged ≥20 years who were diagnosed with CAP of pneumonia severity index (PSI) ≥4 to participate in this single-center prospective cohort study. Patients who presented in respiratory failure or septic shock were excluded. Two emergency physicians performed DUS to obtain DTF and DE measurements. Data was collected to calculate PSI, CURB-65 score, and Infectious Diseases Society of America / American Thoracic Society severity criteria. Study endpoints were taken at development of respiratory failure or 30 days post-ED presentation. Continuous variables were analysed with T-tests, while categorical variables were analysed with chi-square tests. Further logistic regression and receiver operating characteristic curve analyses were performed to examine ability to predict development of respiratory failure. Intra- and inter-rater reliability was examined with intraclass correlation coefficients (ICCs). Results: Thirteen of 50 CAP patients enrolled developed respiratory failure. DTF was found to be an independent predictor (OR 0.939, p=0.0416). At the optimal cut-off point of 23.95%, DTF had 69.23% sensitivity, 83.78% specificity, 88.57% negative predictive value, and 80% accuracy. Intra- and inter-rater analysis demonstrated good consistency (intra-rater ICC 0.817, 0.789; inter-rater ICC 0.774, 0.781). Conclusions: DUS assessment of DTF may reliably predicts the development of respiratory failure in CAP patients presenting to the ED. Patients with DTF >23.95% may be considered for outpatient management.